Response of Different Synbiotics on Gut Health, Immunity and Growth Performance of Pre-ruminant Buffalo Calves - Sharma, Amit N.; L, Vandana Kumari; Ram, Chand; Mondal, Goutam (Indian Journal of Animal Nutrition, 2020)
The study was conducted to evaluate the response of synbiotics on gut health, immunity and antioxidant status, and growth performance of pre-ruminant Murrah buffalo calves. Twenty-four pre-ruminant Murrah buffalo calves (5-10 d old) having similar body weight (34 to 37 kg), were randomly divided into four groups of six animals in each group. Calves of the control (CON) group were fed basal diet (milk, calf starter and green maize) without any supplementation. Basal diet of the calves were supplemented Â with 3 g inulin+L. plantarum CRD-7 as fermented milk (150 ml) having 108 CFU/ml/calf/day,Â Â 6 g inulin+ L. plantarum CRD-7 as fermented milk (100 ml) having 108 CFU/ml/calf/day, and 9 g inulin+L. plantarum CRD-7 as fermented milk (50 ml) having 108 CFU/mL/calf/day in groups, SYN1, SYN2 and SYN3, respectively. A digestibility trial of five days was carried out after 56 day of experimental feeding. The final body weight (kg), average daily gain (g) and chest girth were higher (P<0.05) in SYN3 as compared to control. Crude protein and dry matter digestibility were higher (P<0.05) in SYN3 group than CON group, while digestibility of other nutrients was similar among the groups. Fecal Lactobacilli and Bifidobacterium count was increased (P<0.05) and coliform count was decreased (P<0.05) in SYN3 groups than CON group. Cell mediated immune response and fecal score was higher (P<0.001) in SYN3 than CON group. It was concluded that supplementation of 9 g inulin with 50 g L. plantarum CRD-7 as fermented milk (50 ml) having 108 CFU/mL/calf/day to pre-ruminant calves will improve immunity and growth performance.